Quality Assurance System for Pharmaceutical Wholesalers (PBF) by Implementing Good Drug Distribution Methods (CDOB) in Jayapura City - Makaba, Sarce; Tandililing, Susanty; Medyati, Novita; Irab, Semuel Piter; Anggai, Martapina; Tingginehe, Rosmin (PT FORMOSA CENDEKIA GLOBAL, 2024)
Good Drug Distribution Methods (CDOB) aim to ensure quality along the drug distribution route according to the requirements and purposes of use. This study aims to evaluate the implementation of CDOB in 22 Pharmaceutical Wholesalers (PBF) in Jayapura City. This quantitative descriptive research uses a questionnaire to assess 9 aspects of CDOB. The results showed that the quality management aspect: 77.3% PBF was qualified, organization, management, and personnel: 59.1% PBF was qualified, building and equipment: 22.7% PBF was qualified, operations: 40.9% PBF was qualified, self-inspection: 50% PBF was qualified, product complaints, returns, suspected counterfeiting, and drug recalls: 72.7% PBF was qualified, transportation: 90.9% PBF was qualified, documentation: 72.7% of PBFs are eligible.